Internet regulation across ASEAN. - Chin, Catherine Kai Koon. (2008)
This project looks into how the Internet is regulated in ASEAN. Apart from specific Internet laws, existing domestic laws were also examined. A comparison and analysis of the regulations across the countries were also made.